2018
DOI: 10.3390/polym10111281
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ziegler–Natta-Type Catalytic System—TiCl4/2,2′-Dimethoxy-1,1′-Binaphthalene/Et3Al2Cl3/Bu2Mg for Production of Ultrahigh Molecular Weight Polyethylene Nascent Reactor Powders, Suitable for Solvent-Free Processing

Abstract: A series of ultrahigh molecular weight polyethylenes with viscosity-average molecular weights in the range of 1.6–5.6 × 106 have been prepared by using a novel Ziegler–Natta-type catalytic system—TiCl4/2,2′-dimethoxy-1,1′-binaphthalene/Et3Al2Cl3/Bu2Mg at different temperatures (Tpoly) in the range between 10 and 70 °C in toluene. The morphology of the nascent reactor powders has been studied by scanning electron microscopy, wide-angle X-ray diffraction, and the DSC melting behavior. Polymers are suitable for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These values are equal to the ultimate mechanical properties reported by using a homogeneous Cat. 1 /MAO catalytic system and far superior than any other heterogeneous catalytic system reported for the synthesis of solid-state processable UHMWPE. ,,,, …”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…These values are equal to the ultimate mechanical properties reported by using a homogeneous Cat. 1 /MAO catalytic system and far superior than any other heterogeneous catalytic system reported for the synthesis of solid-state processable UHMWPE. ,,,, …”
Section: Resultsmentioning
confidence: 95%
“…2 The so far reported heterogeneous Ziegler−Natta type catalytic system reached up to 2.5 GPa in terms of tensile strength and 136 GPa for tensile modulus with the highest activity. 26 Borealis AG, Austria, together with Rastogi and Romano also patented a modified Ziegler−Natta catalyst for solid-state processable UHMWPE. 18 Tuskaev et al reported the highest values of 2.8 and 145 GPa in terms of tensile strength and tensile modulus, respectively, for heterogeneous catalytic systems.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations